Efeito de vernizes fluoretados suplementados com nanopartículas de Trimetafosfato de Sódio sobre o desgaste dental erosivo: estudo in vitro - Veri, Isabela Vecchiatti [UNESP] (2018)
The present study evaluated the effect of fluoride varnishes supplemented with nanosized sodium trimetaphosphate (TMP) on enamel erosive wear in vitro. Bovine enamel blocks (n = 50) were selected by surface microhardness (SH) and randomly divided into 5 experimental groups (n=10/group), according to the varnishes to be tested: (a) Placebo (without F or TMP), (b) 5% NaF, (c) 5% NaF + 5% micrometric TMP (TMPmicro), (d) 5% NaF + 2,5% nanosized TMP (TMPnano) and (e) 5% NaF + 5% TMPnano. Half of blocks' surface was protected with cosmetic enamel acid resistant (control), while other half was exposed to varnish treatment and erosive wear (ERO). Blocks received a single varnish application, being immersed in artificial saliva for 6 h. Following, varnishes were removed and all blocks, submitted to 4 daily erosion challenges (ERO, immersion in 0.05 M citric acid, pH 3.2, 90s/cycle, under agitation). Subsequentially, blocks were immersed in placebo dentifrice for 15 seconds. The blocks were analyzed by profilometry. The data were submited to ANOVA and Student-Newman-Keuls' test (p<0.05). The highest values of enamel wear was observed for the blocks treated with the Placebo, followed by 5% NaF + 2.5% TMPnano > 5% NaF > 5% NaF + 5% TMPmicro > 5% NaF + 5% TMPnano, without significant difference between 5% NaF and 5% NaF + 2.5% TMPnano. It was concluded that the addition of TMP to a fluoridated varnish significantly enhances its protective effect against enamel erosion, and that the use of nanoparticles of this phosphate further enhances such effect